Information Model for Auto-generation of Assembly Work Instructions: Using information from manufacturing preparation by increasing system interoperability - Bäckström, William; Westberg, Christopher (My University, 2021)
This thesis aims at finding an information model suitable to handle the data needed for auto-generation of work instructions. The purpose is to enable the generation of work instructions without requiring manual work by production planners, making it possible to better handle the increasing variation in production which the case company Volvo GTO currently faces. The effort is trying to take the digital technology into advantage not only for the sake of the operator but for the sake of the engineers performing the preparation processes. By iterative development together with representatives from the software companies and Volvo GTO, an information model has been developed. A simple demonstrator in Java was designed to develop the model and prove its functionality. A pedal car assembly case taken from closely related research projects has been used in the development process. Finally, the model was implemented within the ThingWorx IoT platform. At this stage, solving interoperability issues between different involved systems turned out to be key to move forward in the process. The most important characteristic of the information model presented is the possibility to break down tasks into smaller elements, representing simpler movements, and let parts and tools be related to these. Input to manikin simulation software has been proven useful for providing such context as well as data from line balancing software. The information model designed is considered relatively simple to expand, both in terms of complexity of the objects and the number of objects. Simulation and planning software used have previously served other main purposes, thus their functionality and interfaces are designed with this in mind. Using a modular design with the IoT platform ThingWorx as centerpiece has proven to help overcome some interoperability issues as its interface is easily adapted to fit a wide range of software. Its flexible handling of data structures enables imported data to be mapped and used for other purposes, like work instructions. The next step is to fit the data to an HMI so that the information model and its abilities can be utilized to support the operator. To increase the technology readiness level, the information model also needs to be verified and most probably extended to be able to serve more complex tasks in assembly.
Keywords: work instructions, information model, system interoperability, cognitive support; Industry 4.0, manikin simulation, manufacturing preparation